Produção de estruvita (MgNH4PO4.6H2O) a partir da urina humana através de precipitação induzida por íons de magnésio - Memelli, Marina Santos (2019)
The physical-chemical process of struvite precipitation is a technique that presents a high potential in the removal of nutrients, from different types of effluents. The objective of the present study was to evaluate the production of struvite (MgNH4PO4.6H2O) from human urine through magnesium ion induced precipitation for use as an alternative fertilizer in agriculture, comparing two commercial compounds with a high magnesium content (MgO and MgCl2) and a low-cost alternative compound, marine brine, as an alternative source of magnesium. The experiment was performed on a laboratory scale using Jar Test. Tests were performed varying the concentration of magnesium, speed of rotation and time of agitation, seeking the best precipitation conditions. The stored human urine presented concentrations of phosphorus and nitrogen of 0.7 and 5.6 g/L, respectively. Precipitation was monitored for pH (9.2-9.7) and temperature (21 - 25.7 °C), reaching a considerable phosphorus removal of 98.9%. It was verified the quality of the crystals generated, with the identification of the mineral of interest - struvite - using the X-ray diffraction. The best-performing assays were 0.45 gMg/L, 100rpm, 10 minutes agitation, and MgO addition. The recovered solids presented purity of 77% (MgO), 60% (Brine) and 52% (MgCl2) of struvite. Brine had the lowest cost of $ 13.96 per kg of struvite.